2021
DOI: 10.2196/21757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Web-Based Group Mindfulness Training on Stress and Sleep Quality in Singapore During the COVID-19 Pandemic: Retrospective Equivalence Analysis

Abstract: Background The COVID-19 pandemic has negatively impacted psychological health. Mindfulness training, which helps individuals attend to the present moment with a nonjudgmental attitude, improves sleep and reduces stress during regular times. Mindfulness training may also be relevant to the mitigation of harmful health consequences during acute crises. However, certain restrictions may necessitate the web-based delivery of mindfulness training (ie, rather than in-person group training settings). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Specifically, mindfulness may aid in self-regulation in terms of coping, while compassion may motivate individuals to regulate their own behavior in the interest of the greater good by following CDC guidelines. Results are aligned with prior findings on the impacts of mindfulness and compassion on coping and mental health, and add to the literature on the benefits of mindfulness and compassion in the COVID-19 pandemic in young adults (Lim et al, 2021;Zheng et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Specifically, mindfulness may aid in self-regulation in terms of coping, while compassion may motivate individuals to regulate their own behavior in the interest of the greater good by following CDC guidelines. Results are aligned with prior findings on the impacts of mindfulness and compassion on coping and mental health, and add to the literature on the benefits of mindfulness and compassion in the COVID-19 pandemic in young adults (Lim et al, 2021;Zheng et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…For example, in a set of four studies with college students, Weinstein & Ryan (2008) found that mindful individuals reported less frequent use of avoidant coping strategies, and in two of four studies, higher use of approach coping. Two studies of mindfulness training showed that training was associated with better coping and less stress during the pandemic (Lim et al, 2021;Zheng et al, 2020).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The number of interventional studies that investigated the impact of mindfulness practices on individuals’ mental health during the COVID-19 pandemic is limited; nevertheless, they have reported promising results. Almost all the reviewed studies were congruently reported that, after participating in mindfulness interventions, the participants’ mental health and well-being improved (Lim et al 2021 ; Zhang et al 2021 ; Weis et al 2021 ; Matiz et al 2020 ; Farris et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To address urgent and unmet psychological needs across several population domains during the COVID-19 pandemic, a novel psychosocial crisis prevention and intervention model should be established using suitable telemedicine technology ( 30 ). The most common forms of intervention include using smartphone APP [like PsyCovidApp ( 31 ), Insight Timer Meditation App ( 32 )], videoconferencing ( 33 , 34 ), internet ( 35 , 36 ), and so on. Mobile applications ( 37 ), videoconferencing ( 38 ), text messaging ( 39 ), and social media ( 40 ) have shown to be useful communication methods for delivering mental health services.…”
Section: Discussionmentioning
confidence: 99%